THE INFLUENCE OF ORGANIZATIONAL CULTURE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE THROUGH WORK MOTIVATION AS AN INTERVENING VARIABLE - Amelia, Anandha; Sahabuddin, Romansyah; Burhanuddin (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2024)
This study aims to examine the influence of organizational culture and work environment on employee performance through work motivation as an intervening variable among the production department employees of PT. Semen Tonasa in Pangkep District. The research method used is quantitative with a descriptive approach and Partial Least Square (PLS) analysis, with a sample of 75 employees. The results show that organizational culture does not influence employee performance, and work motivation does not mediate this relationship. However, the work environment has a positive impact on employee performance, both the work environment and employee performance positively influence work motivation, and work motivation mediates the relationship between the work environment and employee performance.